2014
DOI: 10.1088/0967-3334/35/6/1163
|View full text |Cite
|
Sign up to set email alerts
|

A high accuracy broadband measurement system for time resolved complex bioimpedance measurements

Abstract: Bioimpedance measurements are useful tools in biomedical engineering and life science. Bioimpedance is the electrical impedance of living tissue and can be used in the analysis of various physiological parameters. Bioimpedance is commonly measured by injecting a small well known alternating current via surface electrodes into an object under test and measuring the resultant surface voltages. It is non-invasive, painless and has no known hazards. This work presents a field programmable gate array based high acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 7 publications
0
20
0
Order By: Relevance
“…To measure the velocity of the pulse wave within the arteries, at least two simultaneous bioimpedance measurements are necessary. Kaufmann et al [9] have shown that the usage of measurement frequencies of up to 390 kHz do almost not affect the morphology of the detected pulse wave and lead to similar results. The second intended application is the electrical impedance myography for detecting muscle contractions.…”
Section: Introductionmentioning
confidence: 68%
See 3 more Smart Citations
“…To measure the velocity of the pulse wave within the arteries, at least two simultaneous bioimpedance measurements are necessary. Kaufmann et al [9] have shown that the usage of measurement frequencies of up to 390 kHz do almost not affect the morphology of the detected pulse wave and lead to similar results. The second intended application is the electrical impedance myography for detecting muscle contractions.…”
Section: Introductionmentioning
confidence: 68%
“…Afterwards, the remaining DC offset voltage is removed by a passive 1st-order high-pass filter with a cut-off frequency of f c = 200 Hz. A voltage-controlled current source (VCCS), which is based on the AD8130 (Analog Devices Inc., Norwood, MA, USA) [9,20], converts the voltage signal into an AC current. This current flows via the electrodes through the bioimpedance (Z Bio ) and a shunt resistor (R S = 69.8 Ω).…”
Section: System Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…It is mostly used to estimate the composition of the human body. Further applications are monitoring of the respiration and the cardiac output as well as the detection of arterial pulse waves and muscle contractions [2,3,4,5,6]. For these purposes, several specific bioimpedance measurement systems have been developed and published in the past [3,5,7].…”
Section: Introductionmentioning
confidence: 99%